Forest fires in the Ave Region (NW of Portugal): main outputs from the Adaptaclima project - Gonçalves, António Bento (2013)
The project ADAPTACLIMA - Adaptation to the effects from climate change (Interreg Sudoe) was based on the preparation of a series of studies on forecasting and analyzing the vulnerabilities and potentialities in Southwest European territories, related with the ongoing climate changes. The weather conditions that occur in Portugal, especially during the summer, are favorable to the occurrence of forest fires. However, the ignition and spread of a fire depends on the interaction of several factors besides the weather, namely the presence of fuel and rugged terrain. There is a wide array of studies and evidence that climate is changing and these changes will manifest themselves very differently in various areas of the planet. It is expected that fire regimes immediately respond to climate change and may even outweigh the direct effects of global warming in the patterns of the distribution and productivity of species. In the northwest of Portugal and in particular in the Ave region, one of the main impacts expected from climate change is a substantial increase in the risk of fires. In addition, the period of fire occurrence will extend throughout the year.